The Impact of Physically Active and Pretend Play on Children’s Mental Development and Evolution - Kaliwal, Asadullah (Journal of Social Sciences - Kabul University, 2021)
This qualitative applied research study is inclined to determine the role of sport on mental development of children. The aim of the study is to determine; how much by sport and play the mental development of children can be enhanced up to possible level and which sport play key role in mental development of children. In this research the various research findings reporting the role physical and mental active plays on mental development of children are reviewed and keys answer to the research question are answered. The research finding indicates that physical activity and sport contributes to mental development in children. Reasonable evidence associating is also found that introducing children to athletics has positive effects on cognitive performance in preschools. Sports provide inspired environment to the children which may reinforce the positive behaviors, thought processes, and emotions that promote mental and physical wellness.